Engineering Biology and Society: Reflections on Synthetic Biology. (November 2013) - Calvert, Jane
Synthetic biology, according to some definitions, is the attempt to make biology into an engineering discipline. I ask what is meant by this objective, which seems to have excited and energised many people and encouraged them to start working in the field. I show how synthetic biologists make a point of distinguishing their work from previous genetic 'engineering', which is described as bespoke and artisan. I examine synthetic biologists' accounts of the differences between biology and engineering, which often oppose comprehension to construction. I argue that synthetic biology, like other branches of engineering, aims to meet recognised needs, and to make the world more manipulable and controllable. But there are tensions within the field—some synthetic biologists have reservations about the extent to which biology can be engineered, and ask whether it is necessary to develop a new type of engineering when working with living systems. After exploring these debates, I turn to some of the broader consequences of making biology easier to engineer, particularly the deskilling and democratisation of the technology. I end by arguing that because synthetic biologists are skilled at bringing together both technical and social forces, they are appropriately described as 'heterogeneous engineers'.